An improved ductile fracture model for structural steels considering effect of high stress triaxiality. (15th July 2016) - Kang, Lan; Ge, Hanbin; Fang, Xing
Graphical abstract: Highlights: Effect of high stress triaxiality on ductile fracture behavior of steels is investigated. 10 fracture tests of steel specimens with U- and V-notches are conducted. Three-stage and two-parameter ductile fracture model is improved and its application is validated. Mesh size dependency of U- and V-notch specimens is studied. Abstract: This study presents results of experimental investigation and ductile fracture model for ductile crack initiation, propagation and final failure in structural steels subjected to high stress triaxiality. To this end, uniaxial tension tests on smooth flat bars, U-notched specimens and V-notched specimens are conducted. Nonlinear finite element analysis of the notched specimens is carried out to obtain the stress triaxiality distributions and histories of notch tip and center of specimens. Based on the previous three-stage and two-parameter ductile fracture model proposed by the authors, the equivalent plastic displacement at element failure during simulations is obtained by notched specimen tests, and an improved ductile fracture model is presented considering the effect of high stress triaxiality during both the plastic stage and the softening stage. The relationship between the equivalent plastic displacement at element failure and nonuniform ratio (nonuniform ratio is the ratio of the average value of stress triaxiality of notch tip and center) is determined by a series of tests and analyses. Detailed finite element analyses that employ the improved ductile fracture model are shown to predict ductile fracture behavior under high stress triaxiality with good accuracy across the mesh sizes, notch radii, and notch degree in terms of ductile crack initiation point, ultimate load point and load-displacement curve.